Pre-radiographic MRI findings are associated with onset of knee symptoms: the most study. - Javaid, M; Lynch, J; Tolstykh, I; Guermazi, A; Roemer, F; Aliabadi, P; McCulloch, C; Curtis, J; Felson, D; Lane, N; Torner, J; Nevitt, M (2010)
OBJECTIVE: Magnetic resonance imaging (MRI) has greater sensitivity to detect osteoarthritis (OA) damage than radiographs but it is uncertain which MRI findings in early OA are clinically important. We examined MRI abnormalities detected in knees without radiographic OA and their association with incident knee symptoms. METHOD: Participants from the Multicenter Osteoarthritis Study (MOST) without frequent knee symptoms (FKS) at baseline were eligible if they also lacked radiographic features of OA at baseline. At 15 months, knees that developed FKS were defined as cases while control knees were drawn from those that remained without FKS. Baseline MRIs were scored at each subregion for cartilage lesions (CARTs); osteophytes (OST); bone marrow lesions (BML) and cysts. We compared cases and controls using marginal logistic regression models, adjusting for age, gender, race, body mass index (BMI), previous injury and clinic site. RESULTS: 36 case knees and 128 control knees were analyzed. MRI damage was common in both cases and controls. The presence of a severe CART (P=0.03), BML (P=0.02) or OST (P=0.02) in the whole knee joint was more common in cases while subchondral cysts did not differ significantly between cases and controls (P>0.1). Case status at 15 months was predicted by baseline damage at only two locations; a BML in the lateral patella (P=0.047) and at the tibial subspinous subregions (P=0.01). CONCLUSION: In knees without significant symptoms or radiographic features of OA, MRI lesions of OA in only a few specific locations preceded onset of clinical symptoms and suggest that changes in bone play a role in the early development of knee pain. Confirmation of these findings in other prospective studies of knee OA is warranted.